Hospital psychology and palliative care in cancer patients (Research, Society and Development, 2024)
Introduction: The present study deals with hospital psychology, in the face of hospital grief pain and palliative care performed by the multidisciplinary nursing team, highlighting the role of the psychology professional. According to the (IBGE, 2020) life expectancy has increased to 74 years. In Brazil, 11.8% of the population is elderly, about 23 million people, corroborating the increase in chronic diseases, one of which is cancer. Mainly uterine (CC). Objective: To identify the competencies of the nursing team and the hospital psychologist that are of great importance in the care of cancer patients in palliative care, to describe the role of nursing in women's health care in Brazil. Supporting the characters in this scenario, helping the patient and caregivers to solve pending issues and emotions when experiencing their own finitude. And, thus, allow the patient to have a better quality end of life. Methodology: This is an exploratory-descriptive and qualitative bibliographic research. Scientific publications indexed in the Scielo, Google Scholar, LILACS and Database databases, accessed through the Virtual Library in Health and Psychology, in Jan 2024, were evaluated. Following the inclusion criteria, seven studies published between 2018 and 2023 were selected. Results and Discussion: The data were submitted to content analysis. The articles were described in three categories: 1) the perception of the nursing team; 2) the patient's difficulties; and 3) the actions of the hospital psychologist. The importance of the role of the nursing team and the psychologist in the palliative care of cancer patients was highlighted. Emphasizing that patients and family members should actively participate in the treatment, strengthening bonds of trust and communication. Conclusion: Palliative care is structured as a new form of death management. It was highlighted that the role of the nurse goes far beyond providing care to women during their hospitalization or outpatient treatment. Thus, as the psychologist with patients in the face of finitude. It was also noticed that women often receive late diagnosis and the support of beliefs in the course of treatment.